The effect of blooket game towards students’ vocabulary mastery at the seventh-grade students of SMP-IT Mathla’ul Anwar Malingping in Academic Year 2023/2024 - Barokah, Ikah; Gumelar, Rizdki Elang; Munawaroh, Tatu (CV. Kurnia Grup, 2024)
The research aims to know whether the use of Blooket Game significant effect towards students’ vocabulary mastery at the seventh-grade of SMP-IT Mathla’ul Anwar Malingping or not. The research paper used the quantitative research design with the characteristics of experimental method that is design into two classes. They are experimental and control class. The population of this research is class VII of SMP-IT Mathla’ul Anwar Malingping, they consist of 84 students. The sample of this research is VII-A as a control class consists of 28 students and VII-B as an experimental class consists of 28 students. The total of sample is 56 students. The instrument is a test and data of this research are collected by giving pre-test and post-test. The data is analysed using statistical SPSS 22 program including mean, standard deviation, and t-test. It could be seen from the result of the post-test of experimental and control class. Based on the result of data analysis and interpretation of the research, it is clear there is a significant effect of Blooket Game towards students’ vocabulary mastery at the seventh-grade students of SMP-IT Mathla’ul Anwar Malingping. It can be seen, the minimum score of pre-tests is 32, maximum is 72, mean 53.86, and standard deviation 11.339. while the minimum score of post-tests of experimental class is 68, maximum 96, mean 81.71 and standard deviation 8.105. furthermore, the minimum score of pre-tests of control class is 32, maximum 72, mean 52.71 and standard deviation 11.317. while the minimum score of post-tests of control class is 60, maximum 88, mean 72.57 and standard deviation 6.974. the result of t-test obtained sig.value 0.000 < 0.05. Ha is accepted and Ho is rejected. It can be concluded that there is a significant effect of Blooket Game towards students’ vocabulary mastery.